(untitled) (Journal of the College of Basic Education, 2022)
This study aims at proving that stereotyping is a behavioral tool that goes beyond the time of the conventional meaning, which was associated with modern writings and theories that extend at its best to the fifties by the discoveries of a theorist or borders and concepts the theorists linked to the discovery of platelets in printing in order to prove that stereotyping is a behavioral pattern linked to the individual’s creation secrets, and that it is associatedwith the emergence of the psychological creation of human being and based on reactionary interaction with reality which is based on the variable in accordance withthe changes in the environment, gender and age and being a mean associated with methods of convincing those who are aware of their different dimensions and formations (knowledge, mental, emotional or instinctive formality), which are linked to benefit through the use of linguistic methods and images that may use machination, concealing and concepts stereotyping or fighting by highlighting the facts in which human being behavior might use as a defensive tool to promote a thought or reject another, to correct a behavior or justify an act in case of the psychologicallyconfusing intention or the formation of a collective impression to instill good perceptions or the opposite or a shift from wrong concepts to correct them through mental messages whose influence derives from their influence in the collective thought linguistically, through its composition in images shared in groups and people that will be taken from the Islamic heritage with its differentreferences (Quranic pieces of evidence, propheticor sacred Hadiths narrated byAal Al-Bayt or other pieces of evidence to which these studies resortto prove the above, whether that was in the time of the Holy Quran or the times of the preceded nations) relying on the presentation of their data on the inductive method at a time and the extraction methods at other times as needed. This study relies on two sections; the first section discusses the linguistic and conventional origin to learning the methods that have studied those concepts recently, then figuring the pieces of evidence inductively through identifying their references and how they were discussed to approaching the aim of the study. The second section discusses the stereotyping, how the stereotyped image is made and the defensive methods mentioned in Holy Quran or other referencesin order to confront the negative stereotyping or to rooting the positive stereotyping then coming out with the findings of the study and ending with the list of references that helped in approaching the aims: "he said embark in it, in the name of Allah be its sailing and its anchoring